Addressing vaccine hesitancy in the training of healthcare professionals: Insights from the VAX-TRUST project - Augusto, F. R. (2025)
Background Evidence suggests that healthcare professionals often feel uncomfortable discussing vaccination with patients, largely due to a lack of training on the topic. In line with the scientific evidence gathered from the VAX-TRUST project, it is crucial to invest in training healthcare professionals and developing political measures to effectively address vaccine hesitancy. This paper explores the importance of training healthcare professionals to address vaccine hesitancy and provides concrete strategies for its implementation. Study design A quantitative research design was used. Methods The findings are based on a comprehensive Delphi survey conducted with a panel of 112 experts. Additionally, the study involved practical interventions carried out across seven European countries, engaging a total of 694 participants. These participants included general practitioners (GPs), paediatricians, nurses, as well as medical and nursing students. This robust and diverse dataset provides a well-rounded perspective on the subject matter, ensuring that the insights gained are both extensive and representative of various healthcare professionals across Europe. Results Three key themes emerged from the findings: the need for effective strategies to address communication challenges with vaccine-hesitant individuals, the importance of using evidence-based communication practices to improve these interactions, and the necessity of integrating social scientific knowledge on vaccination into the training of healthcare professionals. Conclusions Training healthcare professionals is essential to equip them with skills and knowledge needed to deal with the complexities of vaccine hesitancy. Evidence was gathered on ways to reflect and act to develop this capacity, namely, by increasing the ability to communicate empathetically, responding to patients' concerns with evidence-based information, and to building stronger and more collaborative relationships with them.